ANALISIS REKRUTMEN TERHADAP PERJANJIAN KERJA LAUT PADA KESELAMATAN KERJA ANAK BUAH KAPAL (ABK) PT RIFJALI SUKSES - Mardiana, Mardiana; Kamsariyati, Kamsariyati (Sekolah Tinggi Manajemen Transportasi (STMT Malahayati Jakarta), 2025)
PT Rifjali Sukses Indonesia which wants to participate in development, especially in the field of sea transportation. In line with efforts to achieve development goals in the economic and social fields, namely to improve a better standard of living both materially and spiritually, special attention is needed to the human resource factor (HR), especially in the protection and welfare of the crew's labour. The crew recruitment process at PT Rifjali Sukses Indonesia is in accordance with the existing theory. The parties responsible for the recruitment process are the Crewing Division and other staff required in the recruitment section. The recruitment methods used by PT Rifjali Sukses Indonesia are internal and external methods, but the company tends to recruit internally because the cost is lower, faster and easier. The internal method uses references from current employees or crew members and the external method uses cooperation from shipping institutions. The recruitment process begins with notifying job vacancies, then using recruitment methods, and finally job applicants come to the PT Rifjali Sukses Indonesia office.